Characteristics and Inter-citation Network of 100 Most Influential Studies on Ocean Acidification: A Bibliometric Analysis. Issue 1 (2nd January 2022) - Sahoo, Sidhartha; Pandey, Shriram
ABSTRACT: In this study, we aimed to evaluate the trends of the most cited articles on ocean acidification using bibliometric techniques and to provide oceanographers and marine scientists a practical guide in assessing the most influential studies published on this domain. Scopus database is used to extract the literature, and detailed analysis was carried out to identify trends and significant of these studies. The top cited article received 3, 183 citations and the least received 201, with a mean of 462 citations. These 100 most-cited papers originated from 34 different countries. The USA ranked top with the highest number of publications followed by Germany and Australia. The top five journals ( Science, PNAS, Global Change Biology, Marine Ecology Progress Series, Nature ) hold 40% of these influential studies. The thematic cluster analysis showed a composite characteristic of the research domain. The study indicated that a limited of the works focus on impact of ocean acidification on food web that needs to be urgently addressed by the oceanographic community. The study of the carbonate system in coastal, oceanic, and estuaries waters, and its ecological and biogeochemical implications are the emerging areas that required attention for the sustainability and maintaining a healthy balance of the marine ecosystem.